2011
DOI: 10.1039/c1cs15100b
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalysed cross-coupling reactions of P-activated enols

Abstract: Transition metal catalysed cross-coupling reactions are ubiquitous in organic chemistry providing an impressive technique for C-C bond formation. Whilst many electrophilic partners have been described for these reactions, aryl and vinyl phosphates, phosphonates and phosphonites can offer advantages in terms of preparation, stability and reactivity profile. This critical review summarises the advances made to date utilising P-activated enols in metal-catalysed cross-coupling reactions (97 references).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 91 publications
0
31
0
Order By: Relevance
“…The combined organic phase was washed with water,b rine, dried (Na 2 SO 4 )a nd concentrated. The obtained crude solid was purified by SiO 2 gel column chromatography (hexane/AcOEt 20:1) to give (4E)-13 as yellow crystals (84 mg 17.6, 22.7, 81.8, 113.2, 115.1, 127.2 (2C), 128.3, 128.6, 128.7 (2C), 142.0, 157.4, 158.1 ppm;I R( neat): ñ max = 2962, 2924, 2218, 1580, 1443, 1377, 1323, 1234, 1063 In ap rocedure similar to the preparation of (E)-7,t he reaction of (Z)-5b-1 (204 mg, 1.00 mmol) in CF 3 2, 22.6, 124.6, 126.7 (2C), 127.1, 128.0 (2C), 143.6, 146.4, 175.3 ppm;I R( neat): ñ max = 2999, 2669, 1657, 1506, 1435, 1308, 1279, 1206, 1153 In ap rocedure similar to the preparation of (E)-8,t he reaction of (Z)-5b-1 (1.43 g, 7.0 mmol) with DIBAL (20.6 mL, 21.0 mmol;1 .02 m in toluene) gave (Z)-8 as ac olorless oil (1.11g,9 8% 3335,2918,1599,1491,1441,1242,997,763,700 In ap rocedure similar to the preparation of (E)-8',t he reaction of (Z)-8 (744 mg, 4.59 mmol) using Ac 2 O( 562 mg, 5.51 mmol), DMAP (28 mg, 5mol %), and Et 3 N(557 mg, 5.51 mmol) gave (Z)-8' as acolorless oil (849 mg, 91 %, E/Z = 2:> 98). 1 3, 20.9, 21.2, 66.7, 125.8, 126.6, 127.9 (2C) In aprocedure similar to the preparation of (E)-14 a,t he reaction of (Z)-8' (102 mg, 0.5 mmol) using MeLi (3.37 mL, 3. 3, 17.3, 21.1, 28.3, 125.7, 128.0 ChemistryOpen 2017, 6,73-89 www.chemistryopen.org 2017 The Authors.…”
Section: (E)-(3-methyloct-2-en-2-yl)benzene [(E)-14 C] (Scheme 4)mentioning
confidence: 99%
“…The combined organic phase was washed with water,b rine, dried (Na 2 SO 4 )a nd concentrated. The obtained crude solid was purified by SiO 2 gel column chromatography (hexane/AcOEt 20:1) to give (4E)-13 as yellow crystals (84 mg 17.6, 22.7, 81.8, 113.2, 115.1, 127.2 (2C), 128.3, 128.6, 128.7 (2C), 142.0, 157.4, 158.1 ppm;I R( neat): ñ max = 2962, 2924, 2218, 1580, 1443, 1377, 1323, 1234, 1063 In ap rocedure similar to the preparation of (E)-7,t he reaction of (Z)-5b-1 (204 mg, 1.00 mmol) in CF 3 2, 22.6, 124.6, 126.7 (2C), 127.1, 128.0 (2C), 143.6, 146.4, 175.3 ppm;I R( neat): ñ max = 2999, 2669, 1657, 1506, 1435, 1308, 1279, 1206, 1153 In ap rocedure similar to the preparation of (E)-8,t he reaction of (Z)-5b-1 (1.43 g, 7.0 mmol) with DIBAL (20.6 mL, 21.0 mmol;1 .02 m in toluene) gave (Z)-8 as ac olorless oil (1.11g,9 8% 3335,2918,1599,1491,1441,1242,997,763,700 In ap rocedure similar to the preparation of (E)-8',t he reaction of (Z)-8 (744 mg, 4.59 mmol) using Ac 2 O( 562 mg, 5.51 mmol), DMAP (28 mg, 5mol %), and Et 3 N(557 mg, 5.51 mmol) gave (Z)-8' as acolorless oil (849 mg, 91 %, E/Z = 2:> 98). 1 3, 20.9, 21.2, 66.7, 125.8, 126.6, 127.9 (2C) In aprocedure similar to the preparation of (E)-14 a,t he reaction of (Z)-8' (102 mg, 0.5 mmol) using MeLi (3.37 mL, 3. 3, 17.3, 21.1, 28.3, 125.7, 128.0 ChemistryOpen 2017, 6,73-89 www.chemistryopen.org 2017 The Authors.…”
Section: (E)-(3-methyloct-2-en-2-yl)benzene [(E)-14 C] (Scheme 4)mentioning
confidence: 99%
“…[1,2] Cross-coupling reactions allow chemists to design andm anipulate delicate and complex molecules. [3][4][5][6][7][8] These reactions have been proved useful for the synthesis of many important products, such as drugs,m aterials, and optical devices. [9][10][11] Recently,i th as been demonstrated that coupling reactions can take place on solids urfaces, known as on-surface synthesis.…”
mentioning
confidence: 99%
“…The related mesylates, [9,10] tosylates, [10,11] and even phosphates [12] have been explored, although with some drawbacks, mostly due to their introduction mode, but also with some success, especially with tosylates. We reasoned that the leaving-group ability of arylsulfonates in the first step (oxidative addition) of the catalytic cycle could easily be tuned with electron-withdrawing substituents.…”
mentioning
confidence: 99%